p53 immunohistochemical staining patterns in oral squamous cell carcinoma (Journal of Pathology of Nepal, 2016)
Background: Mutation of p53 gene is one of the most common events in oral carcinogenesis. Accumulation of p53 protein has also been detected in premalignant lesions.Materials and Methods:  This study included 40 biopsy samples, which were received in department of pathology, Sarojini Naidu Medical College, Agra, to ascertain p53 expression by immunohistochemically, in patients with oral squamous cell carcinomas and to correlate its expression with histological grade, different sites in oral cavity and tobacco intake/smoking habits.Results: Out of 40 biopsies of oral mucosa, 03 showed normal oral mucosa and 37 were diagnosed as squamous cell carcinoma (SCC), most patients were in 5th and 6th decade and majority (86.5%) of oral SCC were males with buccal mucosa being the most common site. There was a statistically significant difference in p53 expression between oral SCC and normal oral mucosa (p value